Conductive metal-organic framework synthesis from metal nanoparticle precursors - Abigail M Lister; Yu Wang; Ben I Armitage; Weishuo Li; Martin R Castell (JPhys Materials, 2025)
Conductive metal-organic frameworks (MOFs) have potential applications as critical functional materials in electronic devices such as chemiresistive sensors, capacitors and batteries. However, the widespread adoption of MOFs in devices is limited by the lack of reliable methods to generate uniform distributions of the MOFs in situ that are strongly adhered to the desired substrates. Here we present a method of synthesising electrically conductive Cu _3 (HITP) _2 and Ni _3 (HITP) _2 MOFs from Cu and Ni metal nanoparticles. The metal nanoparticles are deposited from a magnetron plasma sputtering source onto substrates that include cotton, glass, gold and paper. These nanoparticle-decorated substrates are then immersed in a mildly alkaline solution of the ligand in the presence of an electrolyte. This results in the growth of MOF on the substrate only where the metal nanoparticles were deposited. The described method overcomes problems associated with drop-casting suspensions of the conductive MOF by generating uniform distributions in situ on the substrates. Both MOFs were generated successfully on all four of the substrates, with no preference for conducting or insulating substrates. The mild chemical synthesis environment and proven success with a variety of substrates indicate that the method is likely to be of wide applicability.